16=23⋅B

Rewrite the equation as 23⋅B=16.

23⋅B=16

Divide each term in 23⋅B=16 by 23.

23⋅B23=1623

Simplify 23⋅B23.

Cancel the common factor of 2.

Cancel the common factor.

23⋅B23=1623

Rewrite the expression.

3⋅B3=1623

3⋅B3=1623

Cancel the common factor of 3.

Cancel the common factor.

3⋅B3=1623

Divide B by 1.

B=1623

B=1623

B=1623

Simplify 1623.

Cancel the common factor of 16 and 2.

Factor 2 out of 16.

B=2⋅823

Cancel the common factors.

Factor 2 out of 23.

B=2⋅82(3)

Cancel the common factor.

B=2⋅823

Rewrite the expression.

B=83

B=83

B=83

Multiply 83 by 33.

B=83⋅33

Combine and simplify the denominator.

Multiply 83 and 33.

B=8333

Raise 3 to the power of 1.

B=83313

Raise 3 to the power of 1.

B=833131

Use the power rule aman=am+n to combine exponents.

B=8331+1

Add 1 and 1.

B=8332

Rewrite 32 as 3.

Use axn=axn to rewrite 3 as 312.

B=83(312)2

Apply the power rule and multiply exponents, (am)n=amn.

B=83312⋅2

Combine 12 and 2.

B=83322

Cancel the common factor of 2.

Cancel the common factor.

B=83322

Divide 1 by 1.

B=8331

B=8331

Evaluate the exponent.

B=833

B=833

B=833

B=833

B=833

The result can be shown in multiple forms.

Exact Form:

B=833

Decimal Form:

B=4.61880215…

Solve for B 16=2 square root of 3*B